Nonderivatization analytical method of fatty acids and cis-pinonic acid and its application in ambient PM2.5 aerosols in the greater Vancouver area in Canada - Y. Cheng; Li, S. M. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2005)
A nonderivatization analytical method has been developed to analyze C-6-C-20 fatty acids and cis-pinonic acid on a GC/FID and a GC/MSD using a polar DB-FFAP capillary column. On the GC/FID, the response was highly linear over concentration ranges > 2 orders of magnitude (R-2 = 1.00). Using a mixed solvent of dichloromethane (DCM): methanol (3:1, v/v) and an extraction temperature of 40 degrees C, the method recoveries of the acids from spiked filters were 81-115% based on deuterated surrogates, and the relative standard deviations were < 12%. The recoveries were mainly controlled by the extraction temperature. At 40 degrees C the acids in sample extracts were stable for at least 12 months, while at 80 degrees C, unintended esterization of the acids by methanol was found that reduces their stability in the sample extracts. The analysis of the acids in PM2.5 samples from NIST using this nonderivatization method showed that the efficiency and accuracy were comparable to the derivatization method. Compared with existing derivatization methods,the method is accurate and sensitive, yet simple to use. This method was applied to PM2.5 ambient aerosols collected from a forest site and at a traffic tunnel outlet in the greater Vancouver area in Canada. Total fatty acids (sum of C-6-C-20) in the aerosols were measured as 20.2-138.7 ng/m(3) at the forest site and 100.2-264.6 ng/m(3) at the tunnel site. The cis-pinonic acid concentrations were 1.6-44.2 ng/m(3) in the forest and from below detection to 6.5 ng/m(3) at the tunnel outlet.